2014
DOI: 10.1155/2014/763810
|View full text |Cite
|
Sign up to set email alerts
|

Recent Research and Applications of Numerical Simulation for Dynamic Response of Long-Span Bridges Subjected to Multiple Loads

Abstract: Many long-span bridges have been built throughout the world in recent years but they are often subject to multiple types of dynamic loads, especially those located in wind-prone regions and carrying both trains and road vehicles. To ensure the safety and functionality of these bridges, dynamic responses of long-span bridges are often required for bridge assessment. Given that there are several limitations for the assessment based on field measurement of dynamic responses, a promising approach is based on numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…In the area of structural mechanics, it is mainly the construction of bridges and concrete and earth-fill dams that require complementary physical and numerical simulation approaches to assess specific aspects of design, construction, and structural behaviour of different types of actions/forcing. We refer the reader to the works of Chen and Chen [26], Al-Janabi et al [27] and Ninot et al [28], among many others for more information on this topic.…”
Section: Methodsmentioning
confidence: 99%
“…In the area of structural mechanics, it is mainly the construction of bridges and concrete and earth-fill dams that require complementary physical and numerical simulation approaches to assess specific aspects of design, construction, and structural behaviour of different types of actions/forcing. We refer the reader to the works of Chen and Chen [26], Al-Janabi et al [27] and Ninot et al [28], among many others for more information on this topic.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, numerical approaches have been proposed for analyzing more realistic and thus complex bridges and vehicle systems. In large, numerical approaches to VBI problems including an inertial force of vehicle can be categorized into two types (Chen and Chen, 2014; Deng et al, 2015): (i) Separated representation for each VBI component; (ii) Augmented representation for entire VBI components. Among those two, separated representation first constructs two sets of Equations of Motion (EOM); one system for the bridge and the other system for the vehicle.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of dynamic forces on long span bridges were instigated after the collapse of the famous Tacoma Bridge in USA. Zhiwei Chen et.al [26] pointed out that for long span bridges subjected to multiple loadings, a number of loading combinations should be simulated in assessment of its behaviour. Further, it was reported that validation of numerical simulations with data measured using structural health monitoring system makes the safety assessment more reliable for these types of structures.…”
Section: Introductionmentioning
confidence: 99%